2021
DOI: 10.1161/jaha.120.019486
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‐Specific Deletion of Orai3 Leads to Severe Dilated Cardiomyopathy and Heart Failure in Mice

Abstract: Background Orai3 is a mammalian‐specific member of the Orai family (Orai1‒3) and a component of the store‐operated Ca 2+ entry channels. There is little understanding of the role of Orai channels in cardiomyocytes, and its role in cardiac function remains unexplored. Thus, we developed mice lacking Orai1 and Orai3 to address their role in cardiac homeostasis. Methods and Results We g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A more dramatic cardiac phenotype emerged when Orai3 is removed in adult mice using a tamoxifen-inducible Orai3 cKO mouse, indicating that the loss of cardiac Orai3 is critical for LV function. In a pathological state, Orai3 cKO mice subjected to pressure overload (2 weeks post-TAC) developed a fulminant dilated cardiomyopathy with rapid HF, characterized by interstitial fibrosis and apoptosis [ 86 ]. This has also been confirmed in vivo in two models of adaptive hypertrophy by infusion of isoproterenol for 15 days or by AAB for 28 days in rats.…”
Section: The Soce In the Adverse LV Remodelingmentioning
confidence: 99%
“…A more dramatic cardiac phenotype emerged when Orai3 is removed in adult mice using a tamoxifen-inducible Orai3 cKO mouse, indicating that the loss of cardiac Orai3 is critical for LV function. In a pathological state, Orai3 cKO mice subjected to pressure overload (2 weeks post-TAC) developed a fulminant dilated cardiomyopathy with rapid HF, characterized by interstitial fibrosis and apoptosis [ 86 ]. This has also been confirmed in vivo in two models of adaptive hypertrophy by infusion of isoproterenol for 15 days or by AAB for 28 days in rats.…”
Section: The Soce In the Adverse LV Remodelingmentioning
confidence: 99%
“…The same group also showed that oxidative stress reduced SOCE in hippocampal neurons and that knockdown of Orai1 was protective against glutathione depletion ( Henke et al, 2013 ). In support of these studies, several of the cardiomyocyte-specific KO and overexpression models of STIM and Orai proteins show significant mitochondrial structural abnormalities correlating with reductions in mitochondrial function and alternations in mitochondrial quality control ( Collins et al, 2014 ; Correll et al, 2015 ; Collins et al, 2019 ; Segin et al, 2020 ; Gammons et al, 2021 ). Silva-Rojas et al examined gain of function mutations in both STIM1 and Orai1 and found that this resulted in increased SOCE and promoted abnormal Ca 2+ handling and mitochondrial activity.…”
Section: Metabolic and Mitochondrial Roles Of Stim And Oraimentioning
confidence: 65%
“…More recently, the physiological role of Orai3 has been interrogated in the heart using a cardiomyocyte-specific deletion. Gammons et al ( Gammons et al, 2021 ) showed that both constitutive and inducible cardiomyocyte-specific deletion of Orai3 develop a phenotype consistent with dilated cardiomyopathy, with increased fibrosis, increased mortality, ultrastructural changes in mitochondria, increased mitochondrial fission, and abnormal sarcomeric structure; highlighting a potentially important regulatory role of Orai3 in the heart.…”
Section: Physiological and Pathophysiological Roles Of Stim/orai In T...mentioning
confidence: 99%
“…Loss of Orai3 expression has been reported to lead to ventricular dysfunction progressing to dilated cardiomyopathy and heart failure. Orai3 is required for proper heart function, maintains intact sarcomere formation and mitochondrial function [ 164 ] ( Table 6 ).…”
Section: Physiology and Pathophysiology Of Orai Isoformsmentioning
confidence: 99%